1997
DOI: 10.1074/jbc.272.29.18015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Goα Mutant That Binds Xanthine Nucleotides

Abstract: Several GTP binding proteins, including EF-Tu, Ypt1, rab-5, and FtsY, and adenylosuccinate synthetase have been reported to bind xanthine nucleotides when the conserved aspartate residue in the NKXD motif was changed to asparagine. However, the corresponding single Go␣ mutant protein (D273N) did not bind either xanthine nucleotides or guanine nucleotides. Interestingly, the introduction of a second mutation to generate the Go␣ subunit D273N/Q205L switched nucleotide binding specificity to xanthine nucleotide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…We also showed that the mutant proteins of G 11 ␣X and G 16 ␣X expressed in COS-7 cells interacted with ␤␥ subunits in a XDP-dependent fashion; they only bound ␤␥ when XDP was available, whereas G 11 ␣DN and G 16 ␣DN did not. These results are consistent with previous findings using G o ␣X and G o ␣DN; the single DN mutation resulted in a loss of ability to bind nucleotides, whereas the double DN/QL mutation lead to xanthine nucleotide binding (5). Although the mutation of Asp 3 Asn in the conserved NKXD motif of G protein ␣ subunits was expected to switch the nucleotide specificity of the mutated protein from guanine nucleotide to xanthine nucleotide, according to the available crystal structures of G protein ␣ subunits and other GTP-binding proteins, we observed that the single DN mutation resulted in a protein not able to bind either nucleotides in three G protein ␣ subunits: G o ␣, G 11 ␣, and G 16 ␣.…”
Section: Dominant Negative Inhibition Of G Protein-coupled Receptor Bsupporting
confidence: 83%
See 3 more Smart Citations
“…We also showed that the mutant proteins of G 11 ␣X and G 16 ␣X expressed in COS-7 cells interacted with ␤␥ subunits in a XDP-dependent fashion; they only bound ␤␥ when XDP was available, whereas G 11 ␣DN and G 16 ␣DN did not. These results are consistent with previous findings using G o ␣X and G o ␣DN; the single DN mutation resulted in a loss of ability to bind nucleotides, whereas the double DN/QL mutation lead to xanthine nucleotide binding (5). Although the mutation of Asp 3 Asn in the conserved NKXD motif of G protein ␣ subunits was expected to switch the nucleotide specificity of the mutated protein from guanine nucleotide to xanthine nucleotide, according to the available crystal structures of G protein ␣ subunits and other GTP-binding proteins, we observed that the single DN mutation resulted in a protein not able to bind either nucleotides in three G protein ␣ subunits: G o ␣, G 11 ␣, and G 16 ␣.…”
Section: Dominant Negative Inhibition Of G Protein-coupled Receptor Bsupporting
confidence: 83%
“…Section 1734 solely to indicate this fact. (5,6). 0.5 g of purified G o ␣ was first incubated with 1 g of transducin ␤␥ and 100 g of m2 MAChR membrane in TED buffer with 10 M GDP, 0.1 mM MgCl 2 , and 1 M ATP for 0.5 h. The reaction was started with the addition of 0.1 M GTP␥S (20,000 cpm/pmol) and 100 M carbachol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For several classes of GTP-binding proteins, a strategy was devised where an aspartate to asparagine mutation shifted nucleotide specificity from guanine to xanthine ( Figure 1B). Examples include H-Ras (Zhong et al, 1995), EF-Tu (Hwang and Miller, 1987;Weijland et al, 1993), Ypt1 (Jones et al, 1995), Rab-5 (Hoffenberg et al, 1995;Rybin et al, 1996), FtsY (Powers and Walter, 1995), adenylosuccinate synthetase (Kang et al, 1994) and Goa (although here a second mutation was essential for shifting nucleotide specificity) (Yu et al, 1997). Xanthine nucleotides are only transiently produced during purine metabolism and are not populated as triphosphates in vivo, allowing for separation of the signaling effect of a specific GTPase in the background of other GTPases.…”
Section: Introductionmentioning
confidence: 99%